2013
DOI: 10.1186/2193-8865-3-44
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed-mediated synthesis of gold nanoparticles using Turbinaria conoides and its characterization

Abstract: The synthesis of metal nanoparticles using algae has been unexplored, but it is a more biocompatible method than the other biological methods. Metal nanoparticle synthesis using algae extract shows rapid and non-toxic process which resulted to nano sizes having the greatest potential for biomedical applications. In this investigation, we studied the green synthesis of gold nanoparticles using the algae extract of Turbinaria conoides. Green synthesis of gold nanoparticles was preliminarily confirmed by color ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(116 citation statements)
references
References 33 publications
(37 reference statements)
12
84
0
2
Order By: Relevance
“…Also, the time taken for AgNPs formation very fast (less than 3 min). These result are agree with many investigators (Rajeshkumar et al, 2012 andAbdel-Raouf et al, 2013 ) who reported that the appearance of dark brown color in solution. Also, Johnson et al (2015) reported formation of silver nanoparticles in a few mint, and Bhimba et al (2014) and who suggested the time formation of silver nanoparticles 10 min at 121ºC.…”
Section: Resultssupporting
confidence: 82%
“…Also, the time taken for AgNPs formation very fast (less than 3 min). These result are agree with many investigators (Rajeshkumar et al, 2012 andAbdel-Raouf et al, 2013 ) who reported that the appearance of dark brown color in solution. Also, Johnson et al (2015) reported formation of silver nanoparticles in a few mint, and Bhimba et al (2014) and who suggested the time formation of silver nanoparticles 10 min at 121ºC.…”
Section: Resultssupporting
confidence: 82%
“…It is also possessed other essential components, digestible proteins along with mineral salts (K, Ca, and Fe) and polyunsaturated fatty acids. Apart, it has a wealthy source of dietary fiber content with iodine which is play an immense role in enhancing the food quality and biochemical homeostasis [8]. Hence, the cytotoxicity of T. conoides was reported in ethyl acetate extract due to its oxygenated fucosterols [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The intense peak of 631.87 cm −1 shows the C-Cl group of alkyl halides [21]. After the bioreduction, there is a shift in the absorption band of 3295.…”
Section: Discussionmentioning
confidence: 99%